The Influence of Market Segmentation on the Selection of Services at Bank Syariah Indonesia: A Case Study of Palembang City - alysha chika yuri; yusleli herawati; muhammad yusuf (Department of Business Administration Politeknik Negeri Sriwijaya, 2022)
This study was conducted to analyze the influence of market segmentation on service selection at Bank Syariah Indonesia (BSI) in Palembang City. A quantitative approach was used through data collection using questionnaires distributed to potential customers. Segmentation criteria included demographic and psychographic variables. Multiple regression analysis was applied to identify significant factors influencing potential customers' service selection. The results showed that demographic factors such as age and income, as well as psychographic aspects such as lifestyle and social class, significantly influenced banking service selection. These findings suggest that BSI can improve its marketing strategy by focusing on targeted market segments to better meet the needs of potential customers in Palembang.